The performance of pipeline ploughs traversing seabed slopes. (15th January 2018) - Bransby, M.Fraser; Barlow, David T.; Brown, Michael J.; Davidson, John; Brankin, Stuart; Robinson, Scott
Abstract: Ploughing is a method used to bury pipelines beneath the seabed. In this method, a large purpose built plough is pulled by a support vessel to create a trench into which a pipeline is lowered. The soil that has been removed is then placed or back filled over the pipeline to provide thermal insulation, protective cover and to prevent upheaval buckling (UHB) due to pipeline thermal expansion. The majority of previous research effort has focussed on the behaviour of ploughs on level seabeds and has not investigated common geohazards such as sloping seabeds. There is also limited guidance available to industry on the limitations of ploughing on slopes. This paper reports a series of experimental tests conducted to investigate how ploughs may behave when seabed slopes are encountered and ploughing has to traverse cross-slope. The results show that ploughing operations can still be undertaken when traversing a slope but that the efficiency of operations is reduced with increasing slope inclination, leading to a reduction of trench depth and spoil heap sizes on steeper slopes. This may result in reduced pipeline cover depths on slopes if these effects cannot be mitigated. Highlights: Modelling the effects of traversing inclined slopes on offshore pipeline ploughing. Increasing slope inclination does not limit the ability of the plough to perform. Final trench depth is significantly decreased with sloping angle. The risk to plough operation increases with increasing slope inclination. Slopes at all inclinations should undergo a geotechnical study to assess the risks to operations.